The Joints of Economic Strength According To Ibn Khaldun - Nurul Mauludiyah; Warsidi Warsidi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2023)
Man must work to make the necessities of life. The more actively people try to use knowledge and skills, it will make it easier for themselves to life. The Covid-19 pandemic is very influential for the economy of the community. Many people experience a decrease in income and even job loss, so having extensive knowledge and qualified skills is very important to be able to survive in difficult situations. Ibnu Khaldun in the book of Muqaddimah, describes the various skills that become the joints of economic strength, namely agricultural skills, architectural skills, carpentry skills, spining and sewing skills, obstetrics skills, and medical expertise. People who have special skills and are able to take advantage of opportunities according to current conditions will be easier to get income in meeting their needs.